2012
DOI: 10.1093/jjco/hys066
|View full text |Cite
|
Sign up to set email alerts
|

Contactin-1 (CNTN-1) Overexpression is Correlated with Advanced Clinical Stage and Lymph Node Metastasis in Oesophageal Squamous Cell Carcinomas

Abstract: Objective: Oesophageal squamous cell carcinoma is one of the deadliest malignancies worldwide. Contactin-1, a neural adhesion molecule, is implicated in tumour invasion and metastasis. The purpose of this study was to investigate the expression of CNTN-1 in normal and cancerous oesophageal tissue, and the potential relevance to clinicopathological features. Methods: Thirty normal oesophageal tissue samples and 82 primary oesophageal squamous cell carcinoma tissue samples were included in this study. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
2
27
2
Order By: Relevance
“…In oesophageal cancer, cell proliferation and migration induced by VEGF-C are reversed by CNTN-1 silencing, which suggested that VEGF-C promotes the development of oesophageal cancer by regulating CNTN-1 expression [20]. The comparison of CNTN-1 expression between normal oesophageal tissue samples and primary oesophageal squamous cell carcinoma tissue samples using IHC demonstrated that CNTN-1 was correlated with stage, lymph node metastasis, and lymphatic invasion [21]. Additionally, CNTN-1 expression was found to be significantly associated with the overall survival and the disease-free survival of patients with oral squamous cell carcinoma (OSCC) [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In oesophageal cancer, cell proliferation and migration induced by VEGF-C are reversed by CNTN-1 silencing, which suggested that VEGF-C promotes the development of oesophageal cancer by regulating CNTN-1 expression [20]. The comparison of CNTN-1 expression between normal oesophageal tissue samples and primary oesophageal squamous cell carcinoma tissue samples using IHC demonstrated that CNTN-1 was correlated with stage, lymph node metastasis, and lymphatic invasion [21]. Additionally, CNTN-1 expression was found to be significantly associated with the overall survival and the disease-free survival of patients with oral squamous cell carcinoma (OSCC) [22].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent study revealed that CNTN-1 was associated with invasive ability and to inversely correlate with the prognosis of lung adenocarcinoma patients, and it was proposed to function in the invasion and metastasis of lung adenocarcinoma cells via RhoA-mediated mechanisms [19]. Studies in oesophageal squamous cell carcinoma [20,21], oral squamous cell carcinoma [22], and gastric cancer [23] further confirmed that CNTN-1 plays a critical role in the development, progression, and pathogenesis of these tumours.…”
mentioning
confidence: 94%
“…Recently, CNTN-1 was demonstrated to be able to promote invasion, metastasis and proliferation in prostate cancer [43], thyroid cancer [44], gastric cancer [35, 45-46], lung cancer [32-33], esophageal squamous cancer [30, 47], and oral squamous cancer [31]. Additionally, in our previous studies, CNTN-1 was found to enhance the metastasis, invasion, and chemoresistance of lung cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the abnormal expression of CNTN-1 was reported to be closely correlated with carcinogenesis and tumor progression [11, 30-34]. Furthermore, the elevated expression of CNTN-1 was demonstrated to facilitate metastasis of MKN45 gastric cancer cells via activation of the EMT process [35].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in addition to L1CAM, increased expression of contactin 1 (CNTN1 and F3/contactin) was detected in lung carcinoma. CNTN1 promoted lung cancer metastasis (11,12) and its expression associated with poor prognosis for patients with lung carcinoma, esophageal, and oral squamous cell carcinomas (11,13,14). Nevertheless, to the best of our knowledge, the role of CNTN1 in prostate cancer progression and metastasis is unknown.…”
Section: Introductionmentioning
confidence: 99%